STUDY OF THE PROPERTIES OF OVERBURDENED ROCKS FROM COAL MINING: OVERBURDEN – AS A RAW MATERIAL IN THE PRODUCTION OF CERAMIC BRICKS (GEOMATE Journal, 2023)
With the development of industry, the amount of man-made waste is growing rapidly. It is necessary to develop energy-efficient resource-saving technologies for use in the processing of. Research in past years has proved the possibility of using coal industry wastes as burning and baking additives in the production of ceramic products. The purpose of this work is to review the properties and discuss the options for using overburden as the main raw material in the production of ceramic bricks. Overburden requires a small amount of organic and chemical additives to adjust its technological properties. This research is due to the need to solve environmental, economic and technological problems in the utilization of overburdened rocks from coal mining. The physical and mechanical properties as well as chemical and mineralogical compositions of overburden have been investigated. Due to the heterogeneity and non-wettability of raw materials in water, it is necessary to grind them. The structural-mechanical characteristics and molding properties using highly mineralized carbonaceous rocks as a solid additive and aluminum oxychloride as a liquid additive have been studied.  The obtained products with the use of additives have higher indicators: compressive strength 33.6-48.2 MPa, frost resistance 50-100 cycles, and water absorption 7.0-10.8. Thus, the results of the research prove the possibility of producing high-quality ceramic bricks from overburden, which will help to significantly reduce the cost of production, compensate for the lack of high-grade clay raw materials, and improve the environmental situation. Nevertheless, further research and technological developments are needed.